2019
DOI: 10.3758/s13414-018-01654-8
|View full text |Cite
|
Sign up to set email alerts
|

Detection measures for visual inspection of X-ray images of passenger baggage

Abstract: In visual inspection tasks, such as airport security and medical screening, researchers often use the detection measures d' or A' to analyze detection performance independent of response tendency. However, recent studies that manipulated the frequency of targets (target prevalence) indicate that d a with a slope parameter of 0.6 is more valid for such tasks than d' or A' . We inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 61 publications
1
12
0
Order By: Relevance
“…Wolfe et al (2007) proposes a z ROC slope of 0.6, which indicates that the noise (target-absent) distribution has a smaller standard deviation than the signal-plus-noise (target-present) distribution. Further publications (Van Wert et al, 2009; Godwin et al, 2010) have reported z ROC slopes similar to those reported by Wolfe et al (2007) while a study reported by Wolfe and Van Wert (2010) found a slope of 0.56 and a study by Sterchi et al (2019) a slope of 0.5 to fit the data more accurately. In our study, data from the basic visual search task (L/T-letter search task) were analyzed under the assumption of an equal variance model using d ′, whereas data from the X-ray image inspection task SBST were analyzed under the assumption of an unequal variance model with a z ROC slope of 0.5 using d a 1 .…”
Section: Methodssupporting
confidence: 60%
“…Wolfe et al (2007) proposes a z ROC slope of 0.6, which indicates that the noise (target-absent) distribution has a smaller standard deviation than the signal-plus-noise (target-present) distribution. Further publications (Van Wert et al, 2009; Godwin et al, 2010) have reported z ROC slopes similar to those reported by Wolfe et al (2007) while a study reported by Wolfe and Van Wert (2010) found a slope of 0.56 and a study by Sterchi et al (2019) a slope of 0.5 to fit the data more accurately. In our study, data from the basic visual search task (L/T-letter search task) were analyzed under the assumption of an equal variance model using d ′, whereas data from the X-ray image inspection task SBST were analyzed under the assumption of an unequal variance model with a z ROC slope of 0.5 using d a 1 .…”
Section: Methodssupporting
confidence: 60%
“…To complete the performance picture, we also calculated the corresponding performance in terms of signal detection theory measures, i.e., sensitivity (d a , as specified in Sterchi et al 2019 ) and the response criterion C (for calculation see Stanislaw and Todorov 1999 ). As some condition x participant combinations produced perfect hit rates, we loglinear corrected all hit and false alarm rates (Hautus, 1995 ).…”
Section: Resultsmentioning
confidence: 99%
“…Pilot training is another well-studied area in eye tracking research [ 77 , 78 , 79 ]. Only a few studies applied eye tracking to scanning and decision-making tasks outside the cockpit, including air-traffic control [ 80 , 81 ] and airport luggage screening [ 82 , 83 , 84 ].…”
Section: Literature Reviewmentioning
confidence: 99%